La intersecció entre la pragmàtica i l'adquisició de segones llengües - Bardovi-Harlig, Kathleen (Caplletra. Revista Internacional de Filologia, 2003)
This article provides a review of research in the acquisition of pragmatic knowledge by second language learners. It begins with a definition of pragmatics and second language acquisition that emphasizes the complex relationshipbetween the acquisition of grammar and language use. After examining four possibilities of relationships between pragmatics and language development, the author reviews past and current research focusing on the following topics: the study of pragmatic development, the identification of speech acts, the influence of host and foreign environments, the role of the first and second languages, and speaker interaction.